Electroporation Enhanced Effect of Dystrophin Splice Switching PNA Oligomers in Normal and Dystrophic Muscle - Camilla Brolin; Takehiko Shiraishi; Pernille Hojman; Thomas O Krag; Peter E Nielsen; Julie Gehl (Elsevier, 2015)
Peptide nucleic acid (PNA) is a synthetic DNA mimic that has shown potential for discovery of novel splice switching antisense drugs. However, in vivo cellular delivery has been a limiting factor for development, and only few successful studies have been reported. As a possible modality for improvement of in vivo cellular availability, we have investigated the effect of electrotransfer upon intramuscular (i.m.) PNA administration in vivo. Antisense PNA targeting exon 23 of the murine dystrophin gene was administered by i.m. injection to the tibialis anterior (TA) muscle of normal NMRI and dystrophic mdx mice with or without electroporation. At low, single PNA doses (1.5, 3, or 10 µg/TA), electroporation augmented the antisense exon skipping induced by an unmodified PNA by twofold to fourfold in healthy mouse muscle with optimized electric parameters, measured after 7 days. The PNA splice switching was detected at the RNA level up to 4 weeks after a single-dose treatment. In dystrophic muscles of the MDX mouse, electroporation increased the number of dystrophin-positive fibers about 2.5-fold at 2 weeks after a single PNA administration compared to injection only. In conclusion, we find that electroporation can enhance PNA antisense effects in muscle tissue.